Surgical management and postoperative outcome of patients with gastric pathologies in three hospitals in the city of Douala - Engbang, Jean Paul; Essola, Basile; Ateba, Marcel Ralph; Chasim, Christian Beugheum; Massom, Gertrude Annie; Ngowe, Marcelin Ngowe (International Surgery Journal, 2022)
Background: To bring out the different surgical approach and to appreciate the post-surgery outcome of patients with gastric pathologies in three Douala’s hospitals. Methods: This retrospective and analytic study has been carryout from January 1st 2010 to November 31st 2019 in three healthcare centers in Douala. Patients’ records who had presented a surgical gastric pathology were included in our study and patients with incomplete filled records were excluded. Statistical analysis was been realized by means of the SPSS 23.0. Results: We selected 158 files of gastric perforation (85.4%), 17 of gastric stenosis (9.2%), and 10 of gastric cancers (5.4%). The mean age of occurrence of gastric perforation in our sample was 42.11±16.5 years and for stenosis was 43.65±23.3 years with a male predominance for these two pathologies. For the cancerous patients the mean age was 54.70±7.5 years with a sex ratio of 1. Simple suture was the most used surgical technique in perforation, pyloromyotomy was done in gastric stenosis. Total gastrectomy and gastrojejunostomy were the most practiced in cancer cases. The death rate varied from 15.8% with perforation to 40% with cancer. The associated factors to complications were age (p=0.002) and duration of hospitalization (p=0,004) in gastric perforation. Conclusions: Gastric perforation was the most frequent pathology affecting mostly traders. The surgical approach was thus pathology dependent.